Plantaginaceae endémicas del Perú - León, Blanca (2006)
The Plantaginaceae are represented in Peru by two genera and 14 species (Brako & Zarucchi, 1993), mainly herbs. Here we recognize three endemic taxa in the genus Plantago. These endemic taxa are found in Subtropical Costal Desert, Desert Shrubland, Paramo and Mesoandean, between 350 and 4100 m elevation. Apparently, none endemic Plantaginaceae have been recorded in the Peruvian System of Protected Natural Areas.